2019
DOI: 10.2298/gensr1901357n
|View full text |Cite
|
Sign up to set email alerts
|

Maize resistance to ear rot caused by Aspergillus parasiticus

Abstract: The fungus Aspergillus parasiticus produces aflatoxins, the most important group of mycotoxins considering their potential toxicity that may cause cancer in humans. Prevention is the most important and economically most beneficial practice in the reduction of fungal growth and mycotoxin production. Due to that, the development of resistant maize genotypes is the most effective method. The aim of the present study was to analyse the resistance of maize hybrids to pathogenic and toxigenic A. pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…Bio-compost decreased the relative abundance of Stachybotrys, which is a plant pathogenic fungus and indoor pollution fungus that can easily cause human diseases [46]. High dosage of the biocompost decreased the relative abundance of Aspergillus that can cause ear rot in plants [47]. The LEfSe analysis showed that Pezizales within Ascomycota under EMI treatment was significantly higher than other treatments because Pezizales preferred habitats with available organic compounds, and are stimulated by compost correction [48].…”
Section: Bio-compost Changed the Dominant Community Representatives A...mentioning
confidence: 99%
“…Bio-compost decreased the relative abundance of Stachybotrys, which is a plant pathogenic fungus and indoor pollution fungus that can easily cause human diseases [46]. High dosage of the biocompost decreased the relative abundance of Aspergillus that can cause ear rot in plants [47]. The LEfSe analysis showed that Pezizales within Ascomycota under EMI treatment was significantly higher than other treatments because Pezizales preferred habitats with available organic compounds, and are stimulated by compost correction [48].…”
Section: Bio-compost Changed the Dominant Community Representatives A...mentioning
confidence: 99%
“…These results were in line with previous studies that indicated that application of organic amendments (compost) could suppress the abundance of soilborne pathogens [ 63 ]. Moreover, compost showed a significantly decreased relative abundance of Aspergillus at the ripening stage (S3), which can prevent barley seed rot [ 64 ].…”
Section: Discussionmentioning
confidence: 99%